Spatial information analysis of characteristics of soil trace element contents in high incidence areas of birth defects - ZHANG Zhuo-dong; ZHANG Ke-li; WU Ji-lei; ZHANG Ting; ZHENG Xiao-ying (浙江大学学报. 农业与生命科学版)
Based on the correlation analysis between the distribution of soil element contents and birth defects, to study the anomaly characteristics of soil elements in high incidence areas of birth defects, and provide scientific basis and new approach for the screening of sensitive factors that induce birth defects, two counties Zhongyang and Jiaokou of Shanxi Province were selected as research area, according to the investigation route and villages of epidemic, soil samples were collected in every village, the contents of 16 kinds of elements in the soil, Al, As, Ca, Cu, Fe, K, Mg, Mo, Na, Ni, Pb, Se, Sn, Sr, V, Zn were measured. ArcGIS 9.0 software was used to analyze the distribution of 96 samples of birth defects incidences and contents of 16 kinds of soil elements by thematic mapping, Kriging interpolating, and overlay analysis. Results show that the incidences of birth defects and the contents of the soil elements had similar spatial variation tendency. The contents of V, Se, Mo, As, Mg, Na elements had considerable spatial correlation with the incidence of birth defects. The low contents of V and Se and high contents of Mo and As in soil may be the cause of high incidence of birth defects. The results above verified the correlation between anomaly contents of soil elements and birth defects.